A new species of Hyperolius Rapp, 1842 (Anura: Hyperoliidae) from the Serra da Chela mountains, south-western Angola - Conradie, Werner; Branch, William R.; Measey, G. John; Tolley, Krystal A. (Zootaxa, 2012)
A new species of African reed frog (genus Hyperolius Rapp, 1842) is described from a high altitude, forested gorge in theSerra da Chela mountain range near the village of Humpata, Lubango area, Huila Province, south-western Angola. It iscurrently only known from its type locality. Phylogenetic reconstruction using the mitochondrial 16S marker reveals thatit is the sister taxon of the poorly known Hyperolius cinereus (>4% sequence divergence) also described from Angola, andforms part of a larger clade comprising H. platyceps. The new species is distinguished from other closely related Hyperolius species by genetic divergence, vocalisation, an unusual torrent stream habitat, and colouration.